Okamejei picta sp. nov., a new rajid skate from the South China Sea (Rajiformes: Rajidae) - Ng, Shing-Lai; Ho, Hsuan-Ching; Joung, Shoou-Jeng; Liu, Kwang-Ming (Zootaxa, 2023)
A new species of Okamejei is described based on two adult males collected from deep waters in the South China Sea. The new species, Okamejei picta sp. nov., is readily distinguished from most other congeners in having densely scattered black spots on dorsal disc. Okamejei hollandi and O. mengae is quite similar to the new species by their spot patterns on dorsal disc, but the new species differs from the former by a combination of characters: a yellowish brown dorsal surface densely covered with small, circular to irregular-shaped black spots; blotches on dorsal disc indistinct; posterior ocellus absent; ventral disc white; disc length 45.0–47.7% TL; distance between cloaca to caudal-fin tip 53.6–55.1% TL; trunk centra 31; total basal radials 73–76, morphology of clasper terminal skeleton, and lacking component funnel at the clasper end.